2020
DOI: 10.3904/kjim.2019.388
|View full text |Cite
|
Sign up to set email alerts
|

Consensus regarding diagnosis and management of atypical hemolytic uremic syndrome

Abstract: Thrombotic microangiopathy (TMA) is defined by specific clinical characteristics, including microangiopathic hemolytic anemia, thrombocytopenia, and pathologic evidence of endothelial cell damage, as well as the resulting ischemic end-organ injuries. A variety of clinical scenarios have features of TMA, including infection, pregnancy, malignancy, autoimmune disease, and medications. These overlapping manifestations hamper differential diagnosis of the underlying pathogenesis, despite recent advances in underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 92 publications
(134 reference statements)
0
51
0
2
Order By: Relevance
“…aHUS is a life-threatening condition; therefore, TPE should be considered standard care until a firm diagnosis is made [7]. When thrombotic thrombocytopenic purpura (TTP), HUS, and secondary thrombotic microangiopathy syndromes have been ruled out, switching to eculizumab treatment is generally recommended [7,9]. Observational studies of patients with aHUS showed that 56%-67% of adults progressed to ESRD within 1 and 3 years, respectively [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…aHUS is a life-threatening condition; therefore, TPE should be considered standard care until a firm diagnosis is made [7]. When thrombotic thrombocytopenic purpura (TTP), HUS, and secondary thrombotic microangiopathy syndromes have been ruled out, switching to eculizumab treatment is generally recommended [7,9]. Observational studies of patients with aHUS showed that 56%-67% of adults progressed to ESRD within 1 and 3 years, respectively [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that removing these autoantibodies from circulation with TPE may be sufficient for achieving hematologic remission. On the other hand, patients with MCP, THBD, or C3 mutations (90%, 62%, and 43%) could be provided with complete remission with TPE alone, according to the literature [6,7,9]. In our study population, two patients had CHF mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although anemia, thrombocytopenia, and particularly elevations in lactate hydrogenase are frequently observed in patients with COVID‐19, fragmentation hemolysis is not a major feature. This does not, however, exclude a diagnosis of complement‐mediated TMA, as even in active aHUS, schistocytes are not always detected on peripheral blood smear examination 65,66 …”
Section: Evidence Supporting a Role For Complement In Covid‐19‐associmentioning
confidence: 99%
“…Atypical HUS is caused by inborn or acquired genetic defects of genes that are associated with regulation of the complement pathway. Atypical HUS is known to be triggered by factors that induce the activation of complement cascades, including infection, pregnancy, organ transplantation, malignancy, autoimmune disease, and drugs (1). Cases of pregnancyassociated atypical HUS are known to occur during the postpartum period (2).…”
Section: Introductionmentioning
confidence: 99%